2D FE Micromechanics Modelling of Honeycomb Core Sandwich Panels - BETTS, Charles; LIN, Jianguo; BALINT, Daniel; ATKINS, Anthony (Engineering Transactions, 2014)
A repeating unit cell 2D finite element modelling procedure has been established to model the mechanical behaviour of honeycomb core sandwich panels (e.g. Young’s modulus, energy absorbed, etc.). Periodic boundary conditions have been implemented within the model to simulate an infinitely long sandwich panel. An analytical solution using Timoshenko beam theory has been developed to predict the Young’s modulus of the honeycomb core, and this has been compared with the FE model results; it is found that there is good agreement between the two values. The FE model can shed light on the mechanics of more complex 3D metal foams.